The Clinical Value of Serum Anti-Cyclic Citrullinated Peptide Antibodies for Juvenile Idiopathic Arthritis - Xiaolan HUANG,; Zheng XU,; Fengqi WU,; Xiaodai CUI,; Xiaofeng LI,; Xianzi CONG,; Jianglin ZHANG, (Archives of Rheumatology, 2012)
Objectives: This study aims to compare the levels of serum anti-cyclic citrullinated peptide (anti-CCP) antibodies in patients with juvenile idiopathic arthritis (JIA) and adult rheumatoid arthritis (RA) and to discuss the clinical value of these antibodies in the diagnosis of JIA. Patients and methods: This study was performed at the Capital Institute of Pediatrics in Beijing between February 2009 and December 2009. The levels of serum anti-CCP antibodies in 72 patients with JIA (33 boys, 39 girls; mean age 7.6±3.9 years; range 2 to 15.9 years), 65 patients with RA (14 boys, 51 girls; mean age 47±14.3 years; range 17 to 75 years), and 22 healthy children (10 boys, 12 girls; mean age 14.1±0.4 years; range 6.1 to 15.7 years) were measured using an enzyme-linked immunosorbent assay (ELISA). The obtained data along with the clinical data were analyzed. Results: The anti-CCP antibody positive rates for the JIA and RA groups were 12.5% and 73.85%, respectively, whereas the rate for the control group was 0% (p<0.001). The anti- CCP antibody positive rates of the polyarticular, oligoarticular, and systemic JIA groups were 31.25%, 14.8% and 0%, respectively (p<0.001). The rheumatoid factor (RF) positive rates, joint destruction rates, and mean disease courses of the positive and negative anti-CCP antibody groups were 66.7% versus 7.9% (chi-square=118.778, p<0.001), 33.3% versus 6.3% (chi-square=124.778, p<0.001), and 18.1 months versus 13.7 months (t=0.606, p=0.546), respectively. Conclusion: The anti-CCP antibody positive rate in patients with JIA is lower than for patients with RA. However this rate varies significantly according to the subtypes of JIA. Positive anti-CCP antibodies often indicate severe joint destruction.